Discrimination Against Women In The Novel "Cantik Itu Luka " By Eka Kurniawan (Literary Sociology Study) - Indriani, Puput; Najwa Patricia Azzahra (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
A novel is a literary work in the form of long and complex prosewritten in a story. The story in the novel is the reality of life and theauthor's imagination that are interrelated. In this study, researcherswant to examine the novel Cantik Itu Luka by Eka Kurniawan. Thisresearch aims to find out and describe the sociology of literaryworks about the discrimination of women's lives in the colonial erato post-independence Indonesia in the novel Cantik Itu Luka by EkaKurniawan. This descriptive qualitative research method producesdescriptive data as problem solving by presenting the state of asubject or object in the form of written words. The data source inthis research is literature or written data in the form of the novelCantik Itu Luka by Eka Kurniawan. Based on the analysis of thenovel Cantik Itu Luka by Eka Kurniawan, it can be concluded thatthis novel can provide an overview of the discrimination of womenin society. Women experience injustice, physical violence, andsexual exploitation that reflect the social structure at that time.